The Ethics of Fetal Tissue Transplants - Fine, Alan (The Hastings Center report, 1988)
The prospect for widespread therapeutic use of human fetal tissues has aroused strong emotions and prompted several objections. Fetal tissue transplantation circumscribed by medical and moral limits will not erode important ethical values, but the pace of scientific research must not preempt public debate and a verdict consistent with societal values.